2021
DOI: 10.1002/slct.202102194
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Fe‐based MOFs/Polymer Composites for the Photodegradation of Organic Dyes

Abstract: Metals Organic Frameworks (MOFs) are promising crystalline, embrittled materials generally produced in powdering form with varied remarkably functionalities. In contrary, polymers are flexible and processable materials. Therefore, obtaining shaped solids gathering polymer malleability and MOFs properties such as their photocatalytic activities, have attracted many researchers' attention. This work, reports the successful fruitful incorporation of two different Fe-based MOFs into a polymer matrix via a facile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 61 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…Fe-based MOF/polymer composites were reported by Brahmi et al as an efficient photocatalyst for the degradation of organic dyes. The photodegradation was completed (95%) in 30 min under UV-visible light irradiation [ 180 ]. Xiong et al also reported Cd(II) MOFs for the photo-degradation of organic dyes.…”
Section: Photocatalytic Degradation and Its Mechanismsmentioning
confidence: 99%
“…Fe-based MOF/polymer composites were reported by Brahmi et al as an efficient photocatalyst for the degradation of organic dyes. The photodegradation was completed (95%) in 30 min under UV-visible light irradiation [ 180 ]. Xiong et al also reported Cd(II) MOFs for the photo-degradation of organic dyes.…”
Section: Photocatalytic Degradation and Its Mechanismsmentioning
confidence: 99%
“…Reproduced with permission of Ref. [48] In an effort to identify structures exhibiting this highly researched photobleaching property while being disconnected from the chemical structures of historical photoinitiators such as TPO or BAPO, a wide range of structures have been examined during the last decade, as exemplified with cyanines, [49][50][51][52][53][54][55] truxene derivatives, [56] viologen derivatives, [57][58][59] metal organic framework (MOFs), [60][61][62] conjugated polymers, [63] polyoxometalates, [64][65][66] Bodipy, [67][68][69] dithienophospholes, [70,71] perylenes, [72][73][74][75] iron complexes, [61,[76][77][78][79][80][81][82] 2,3diphenylquinoxaline derivatives, [83] diketopyrrolopyrroles, [84][85][86] chromones and flavones, [87][88][89] zinc complexes, [90] pyrrole derivatives,…”
Section: Introductionmentioning
confidence: 99%
“…Metal/metal oxide clusters that are connected through organic linkers constitute their structures. , Moreover, MOFs have high porosity, low density, and large pore volume with a high surface area, which are critical parameters for some applications. For example, MOFs are well-known for their ability to catalyze diverse types of reactions, including polymerizations. Numerous MOF-based catalysts have been previously developed for catalytic polymerization. Moreover, among MOF-based composites, MOF-polymer hybrids have recently gained tremendous attention in the field of composite materials. Typically, many MOFs are more compatible with organic matrixes compared to well-known inorganic nanofillers like silica, alumina, and mesoporous carbon since the organic linkers may interact with the monomers/polymers via different routes. , The mutual combination of MOFs and polymers has created a new field in both polymer and MOF chemistry and technology. The integration of MOFs into a monomer/polymer matrix represents a direct and effective strategy to develop innovative composite materials that combine the exceptional properties of MOFs with the robustness of polymers.…”
Section: Introductionmentioning
confidence: 99%